Psoriasis in children: An insight - Sandipan Dhar; Raghubir Banerjee; Nilesh Agrawal; Sharmila Chatterjee; Rajib Malakar (Wolters Kluwer Medknow Publications, 2011)
Onset of psoriasis in childhood is quite common. Chronicity, inflammation and hyperproliferation are the cardinal features by which the condition establishes its uniqueness. Clearance of disease may be farfetched in most patients and relapse is frequent. Early recognition and management of psoriasis in children and adolescents is vital in therapy in children.